2015
DOI: 10.1371/journal.pone.0121907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Source- versus Household Contamination of Tubewell Water on Child Diarrhea in Rural Bangladesh: A Randomized Controlled Trial

Abstract: BackgroundShallow tubewells are the primary drinking water source for most rural Bangladeshis. Fecal contamination has been detected in tubewells, at low concentrations at the source and at higher levels at the point of use. We conducted a randomized controlled trial to assess whether improving the microbiological quality of tubewell drinking water by household water treatment and safe storage would reduce diarrhea in children <2 years in rural Bangladesh.MethodsWe randomly assigned 1800 households with a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 49 publications
2
74
3
3
Order By: Relevance
“…Safe water storage alone in this previously published trial did however lead to a significant 31% reduction in pediatric diarrhea prevalence compared with the control arm. 49 This finding demonstrates that safe water storage alone, although not sufficient to remove all fecal contamination in drinking water this setting, was sufficient to significantly reduce pediatric diarrheal disease. Future studies should evaluate the efficacy of the CHoBI7 intervention in reducing diarrheal disease prevalence in susceptible pediatric populations.…”
Section: Discussionmentioning
confidence: 90%
“…Safe water storage alone in this previously published trial did however lead to a significant 31% reduction in pediatric diarrhea prevalence compared with the control arm. 49 This finding demonstrates that safe water storage alone, although not sufficient to remove all fecal contamination in drinking water this setting, was sufficient to significantly reduce pediatric diarrheal disease. Future studies should evaluate the efficacy of the CHoBI7 intervention in reducing diarrheal disease prevalence in susceptible pediatric populations.…”
Section: Discussionmentioning
confidence: 90%
“…However, recent studies found that one of these chlorine tablets (NaDCC [33 mg]) can produce a 2 mg/L dose of free chlorine residual in 10 L water. 20 Therefore, we decided to use this chlorination ratio in our experiment; each container was filled with 10 L DWASA water and treated with one chlorine tablet. Then, free and total chlorine concentrations were measured before treatment and at seven time points (30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, 12 hours, and 24 hours) after chlorine treatment using the HACH Pocket Colorimeter ™ II.…”
Section: Methodsmentioning
confidence: 99%
“…In order to control for the potential impact of precipitation on water quality and diarrhoea Levy et al, 2016;Mukabutera et al, 2016), total precipitation within the previous 10 days to each household's survey date was included in analyses as a potential confounder (Ercumen et al, 2015b). Data were downloaded in Network Common Data Format (NetCDF) for each village centroid from Climate Hazards Group InfraRed Precipitation with Station data 2.0 (CHIRPS) (Funk et al, 2015), which comprises daily gridded precipitation data derived from satellite and in-situ station data at 0.05 degree spatial resolution (approximately 5.3km).…”
Section: Precipitation Datamentioning
confidence: 99%